The Business of widening participation : policy, practice and culture - McCaig, Colin; Rainford, Jon; Squire, Ruth (Emerald Publishing Limited, 2022)
Widening access to university has become a major component of education policy in the past few decades, particularly in the UK and Europe. The aim is to make a university education more accessible for people from traditionally under-represented backgrounds and to ensure student bodies reflect the diversity of wider society. This key volume presents, for the first time, a critical analysis of the 'business of widening participation' in a marketised context, featuring contributions from some of the major academic and practitioner researchers in the field. Encompassing how WP policy (as a subset of HE policy) is made, enacted and implemented at various stages, also presented are multiple professional and cultural perspectives on how WP is experienced and understood by those enacting policy. Chapter authors explore how the two aspects of the 'business of widening participation' work together to shape how WP is understood and done, as well as the possibilities for doing otherwise by employing a dual usage of the term 'business' in relation to WP. The first, figurative, usage explores the ways in which WP has been drawn into institutional positionality as HE providers differentiate themselves in the market; the second, literal, usage explores the ways in which WP policy is actuated by HE providers (including 'alternative' providers and FE colleges), state actors and third sector and private organisations increasingly engaged in the delivery of WP interventions and as policy stakeholders in this field. Offering both a comprehensive policy history of widening participation in UK higher education and exploration of how that policy has translated into institutional practices in different contexts, this timely work offers new analysis to academics familiar with the field whilst also offering sufficient background to practitioners who may be less familiar with the historical context and academic debates around WP.